Pengaruh Kualitas Pengungkapan Keuangan dan Struktur Kepemilikan Terhadap Asimetri Informasi - Farma Andiansyah; Slamet Haryono (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2021)
Abstract -The presence of information asymmetry increases transaction costs and reduces liquidity, and reduces the quality of investment decisions taken by investors. So that in turn it weakens the overall function of the market. Accounting disclosure plays a role in mobilizing information from management and investors so as to reduce information asymmetry. In addition, it is hoped that the presence of a concentration of investor ownership can carry out internal monitoring of the company so as to reduce information asymmetry. On the other hand, institutional investors have many incentives to access company information for their trading purposes due to the conflict of interest between outside investors and the board of directors. This study aims to determine the effect of disclosure quality and ownership structure on information asymmetry in companies listed on the Jakrta Islamic Index (JII) during the 2015-2019 period. Based on the results of panel data analysis of the Fixed Effect Model (FEM), it was found that institutional ownership had a significant positive effect on information asymmetry, while the quality of disclosure and ownership concentration did not have a statistical effect on information asymmetry.